Enhanced optimal inventory control policies of perishable products in a retail business: a comparative simulation study under different cost structures. Issue 4 (22nd August 2019) - Heng, Naleak; Chiadamrong, Navee
This paper experiments different replenishment policies of perishable products using simulation-based optimisation approach. The main contribution of this study is to recommend the best replenishment policy and whether enhancing a typical periodic review policy can lead to a better outcome. It was found that enhancing a typical periodic review policy with a backroom and a reorder level can lead to a higher net profit. In some instances, integrating both of them together can outperform implementing them alone, as they can complement each other. The finding also suggests that enhancing the base policy by screening out bad items before reaching the customers may not be so cost-effective if the removed items cannot be sold to generate extra revenue or the loss of goodwill is not the main concern. These findings can help shop managers to make right decisions on the optimal inventory policy in a certain situation under an uncertain environment.